A Symbolic Participation of the Local Community in the Implementation of A PROPER-based Corporate Social Responsibility (CSR) Program - Pera, Yosef Hillarius Timu; Ridwansyah, Yusup (UI Scholars Hub, 2020)
CSR practices continue to grow as a promising alternative development resource, yet still predominantly charitable in nature, preventing them from optimal community empowerment. Therefore, studies and policies at the national and global levels remain in search of the best format to optimize CSR programs’ role in community empowerment. A number of literature show less than optimal active participation and capacity-building of the community if a program is initiated by a directive, top-down approach, providing only a minimal participatory space based on the community’s potentials. Using qualitative method and in-depth interview techniques, this paper finds that the local community participation in PLTU’s CSR implementation is symbolic and characterized by artificiality, mobilization to meet procedures, and more dominant role of elite actors that hampers empowerment and capacity-building of the community at large. The local community’s participation only reaches the level of placation and is not in line with the spirit of the Proper guidelines aimed at achieving the level of partnership. It is due to the company’s approach that tends to be procedural in fulfilling the Proper parameters without providing sufficient space and time to accommodate the community’s aspirations and potentials, the limited program assistances, and the pragmatic society that has lost its communal characters.